MRI of Hands with Early Rheumatoid Arthritis: Usefulness of Three-Point Dixon Sequences to Quantitatively Assess Disease Activity. Issue 1 (10th January 2022) - Kirchgesner, Thomas; Stoenoiu, Maria; Durez, Patrick; Michoux, Nicolas; Vande Berg, Bruno
The use of efficient treatment with a treat-to-target strategy combined with early detection of the disease completely changed the imaging presentation and outcome of newly diagnosed rheumatoid arthritis (RA) patients. Magnetic Resonance Imaging (MRI) has become the reference technique in clinical research to detect and quantify inflammatory involvement of the soft tissues (synovitis and tenosynovitis) and bone marrow (osteitis) along with structural damages of the bone (erosions) in hands of patients with RA. Three-point Dixon MRI may be a valuable alternative to the currently recommended sequences as it yields effective fat signal suppression, high imaging quality and reproducible assessment of disease activity.